The Use of Sunitinib as Maintenance Therapy in a Pediatric Patient With a Poorly Differentiated Thymic Carcinoma. Issue 2 (March 2022) - Romanos-Sirakis, Eleny; Doan, Andrew; Bittman, Mark E.; Webb, Ryan L.; Williamson, Alex K.; Edelman, Morris; Hanson, Derek; Riely, Gregory J.; Fein Levy, Carolyn
Abstract : Background: Thymic carcinomas are rare aggressive mediastinal tumors with a median survival of 2 years. Observation: We present a pediatric patient who was diagnosed with metastatic thymic carcinoma and showed continuous improvement of his primary mass and lung metastases with a regimen of cisplatin/docetaxel followed by long-term maintenance therapy with sunitinib for over 5 years. Conclusions: This report demonstrates a long-term positive treatment effect using chemotherapy followed by sunitinib in an advanced thymic carcinoma. We are not aware of other reports of pediatric patients with metastatic thymic carcinoma treated with sunitinib maintenance who maintained a durable response for this prolonged period of time.